Guests at God's Wedding : Celebrating Kartik among the Women of Benares. - Pintchman, Tracy (State University of New York Press, 2005)
This fascinating look at the sacred Hindu month of Kartik (October-November) as it is celebrated in the city of Benares in North India highlights Kartik-related practices, stories, songs, and experiences particular to women. During Kartik, Hindu women living in and around Benares meet daily to enact a form of ritual worship, or puja, in which they raise the playful Hindu deity Krishna from childhood to adulthood throughout the month, ultimately marrying him to the plant-goddess Tulsi (Basil). Tracy Pintchman explores how women who perform Kartik puja understand and celebrate both Kartik and Krishna in ways that are linked to the desires, hopes, fears, and social realities characteristic of many Hindu women living in the rather conservative social milieu of this region.